2018-2019 Antimicrobial Resistance Pattern in Bacterial Pneumonia at Dr. Soedarsono Hospital Pasuruan - Susanto, Felicia; Purnamawati, Catur Elvi; Riasari, Devvi (Universitaas Brawijaya, 2020)
Pneumonia is the ninth most common disease in dr. Soedarsono Pasuruan Region General Hospital. The resistance of Klebsiella pneumoniae to third-generation Cephalosporins and Streptococcus pneumonia to Penicillin were the topics discussed on World Health Organization’s (WHO) global report for antimicrobial resistance. This study purpose is to analyze the microbial pattern and antimicrobial resistance of bacterial pneumonia from sputum culture. This is a descriptive retrospective study with a total of 59 requests for sputum culture which included a clinical diagnosis of pneumonia. There are 37 male (63%) and 22 female (37%) with the most age group was adult (18-59 years) 39 people (66%) included in this study. Gram-negative bacteria are more common as the cause of pneumonia than gram-positive. Gram-negative bacteria that caused pneumonia in this study are Klebsiella pneumoniae (25.4%), Acinetobacter baumannii (15.3%), dan Enterobacter cloacae complex (15.3%). Gram-positive are Staphylococcus haemolyticus (11.9%), Staphylococcus aureus (8.5%), and Staphylococcus epidermidis (8.5%). The most antimicrobial resistance in gram-negative bacteria is Ampicillin (94.3%) and gram-positive bacteria are Benzylpenicillin (94.1%). The number resistance of Penicillin in gram-negative and gram-positive was high; therefore empirical therapy for pneumonia still uses broad-spectrum antimicrobial like beta-lactam.